2017
DOI: 10.1590/0100-3984.2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of contrast-enhanced spectral mammography for estimating residual tumor size after neoadjuvant chemotherapy in patients with breast cancer: a feasibility study

Abstract: ObjectiveTo assess the feasibility of contrast-enhanced spectral mammography (CESM) of the breast for assessing the size of residual tumors after neoadjuvant chemotherapy (NAC).Materials and methodsIn breast cancer patients who underwent NAC between 2011 and 2013, we evaluated residual tumor measurements obtained with CESM and full-field digital mammography (FFDM). We determined the concordance between the methods, as well as their level of agreement with the pathology. Three radiologists analyzed eight CESM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
3
10
0
1
Order By: Relevance
“…They even found that CESM can better predict complete pathological response better than MRI (Lin's coefficient: 0.81 for CESM and 0.59 for MRI). In another study, performed by Barra et al, they also proved that CESM measurements showed a strong, steady correlation with the pathology residual tumor size (R: 0.76), a value which is slightly higher than that scored by the RECIST 1.1 criteria in the current study [28] (Fig. 7).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…They even found that CESM can better predict complete pathological response better than MRI (Lin's coefficient: 0.81 for CESM and 0.59 for MRI). In another study, performed by Barra et al, they also proved that CESM measurements showed a strong, steady correlation with the pathology residual tumor size (R: 0.76), a value which is slightly higher than that scored by the RECIST 1.1 criteria in the current study [28] (Fig. 7).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies reported nearly similar indices, although they were mainly based on residual tumor size assessment. Barra et al [28] reported no false positive cases and the calculated sensitivity, specificity, PPV, and NPV was 83.33%, 100%, 100%, and 66% respectively. On the other hand, Iotti et al [2] reported no false negative cases with a calculated sensitivity and specificity of 100% and 84%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…English proficiency is crucial for the professional growth of physicians, since it allows adequate access to updated medical information ( 4 , 5 ) , as well as participation in international conferences and meetings. In this context, the main radiology journal in Brazil accepts and had published articles in English ( 6 - 12 ) . Given the lack of studies on bilingual education in radiology, especially musculoskeletal imaging, we were motivated to analyze the integration method of English into radiology instruction.…”
Section: Discussionmentioning
confidence: 99%
“…In the detection of residual disease after NAC, a meta-analysis reported a pooled sensitivity with CEM of 80.7% (95% CI 65.5–90.2%) and a pooled specificity of 94.0% (95% CI = 78.3–98.6%) [ 18 ]. The literature investigating the role of CEM in the assessment of residual breast cancer following NAC continues to increase [ 19 , 20 , 21 , 22 , 23 ]; to the best of our knowledge, this is the first study that aims to evaluate the specific contribution of calcifications in this context. The implications of residual calcifications after NAC are still debated; since some calcifications may represent treated cancer with calcified or necrotic tissue and sloughed cells, their persistence in the tumor bed evaluated exclusively with mammography has not correlated with residual neoplasia [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%